Implementing Campus Indoor Location Tracking System (International Journal of Engineering and Computer Science, 2016)
Digital electronic maps are used to track the location in outdoor and indoor environment. Most of electronic maps are useful for outdoor environment. There is no efficiency technology for search the indoor location. Many smart-phones are used to track the location by electronic map. The electronic maps may be the Google map, GPS navigation, waze and offline GPS maps. These are only useful for outdoor environment. Indoor based location tracking system can be implemented by using the Indoor Atlas Android SDK. It provides an API for developers to create application for inside building navigation. This app also useful for vision it have impaired people because the speech recognition for searched location and also include the event details in indoor based location tracking application. Using this app to find the shortest path for desired location.